Interpreting the pari passu clause in sovereign bond contracts: It's all Hebrew (and Aramaic) to me - Mark L. J. Wright (Federal Reserve Bank of Chicago, 2014)
In this comment, we take a helicopter tour of the history of notions of "equality" and "justice" in sovereign debt restructuring in particular, and in the division of property more generally, and show that these concerns have existed for centuries, if not millennia. We argue that the issue at stake in the interpretation of the pari passu clause is not so much the treatment of holders of identical claims - it is now customary to treat them identically - but whether the holders of different claims should be treated differently. We show that exists a customary "principle of differentiation" that allows creditors with claims that differ in specific ways to be treated preferentially. One of these specific differences concerns debts that have been reduced in value during a previous debt restructuring or default, and based on this principle we conclude that the New York court has, if not completely misinterpreted the meaning of the pari passu clause, then at least misapplied it.
Keywords: D63; F34; K12; 330; sovereign debt restructuring; pari passu; Argentina; inter-creditor equity